Mutant p53: Multiple Mechanisms Define Biologic Activity in Cancer - Kim, Michael Paul; Zhang, Yun; Lozano, Guillermina (Frontiers in Oncology, 2015)
The functional importance of p53 as a tumor suppressor gene is evident through its pervasiveness in cancer biology. The p53 gene is the most commonly altered gene in human cancer; however, not all genetic alterations are biologically equivalent. The majority of p53 alterations involve missense mutations that result in the production of mutant p53 proteins. Such mutant p53 proteins lack normal p53 function and may acquire novel functions, often with deleterious effects. Here, we review characterized mechanisms of mutant p53 gain of function in multiple model systems. In addition, we review mutant p53 addiction as emerging evidence suggests that tumors may depend on sustained mutant p53 activity for continued growth. We also discuss the role of p53 in stromal elements and their contribution to tumor initiation and progression. Lastly, current genetic mouse models of mutant p53 are reviewed and their limitations discussed.